Persons With Disabilities in Self-Employment Served by the Federal/State Vocational Rehabilitation System: Differences Between 2011–2013 and 2017–2019. (April 2023) - Sánchez, Jennifer; Frain, Michael P.; Shirley, Ghari; Rohack, Devin; Pan, Deyu
Persons with disabilities (PWDs) are disproportionately unemployed, underpaid, and underemployed despite their desire and capacity to work. The U.S. federal/state vocational rehabilitation (VR) program, under the supervision of the Rehabilitation Services Administration (RSA), is charged with providing services to assist eligible PWDs (VR consumers) in achieving employment. Despite research showing that VR consumers closed to self-employment (vs. non-self-employment closures) have better outcomes, self-employment is often considered as a last resort. Moreover, some evidence suggests self-employment (like non-self-employment) outcomes are associated with VR consumers' gender and racial/ethnic identity. The objective of this study was to determine trends of case closures in self-employment among PWDs within the VR program from 2011–2013 to 2017–2019 and to examine the effects of gender and race/ethnicity on self-employment outcomes. Variables of interest were obtained from RSA's Case Service Report (RSA-911) data set for 2011, 2012, 2013, 2017, 2018, and 2019. Data were recoded and analyzed. The number of closures in self-employment declined significantly. Weekly earnings in self-employment increased. Time from application to closure in self-employment decreased. Differences in VR self-employment outcomes by race/ethnicity and gender were noted. Efforts should be made to increase competency in self-employment of VR counselors and promote self-employment within the VR program.